(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
This study was accomplished to scrutinize the pollen morphology of 15 species of the genus Artemisia of the family Asteraceae from Gilgit-Baltistan region of Pakistan by means of scanning electron microscopy (SEM). Results revealed pollen grains of Artemisia species with tricolporate shape, and characterized by globular symmetry (ellipsoid ball shaped from equatorial side and three lobed rounds from polar view) with few exceptions. Additionally, the pollens are marked with reduced spinules on their surfaces which are diagnostic character for the genus Artemisia. In this study, seven micromorphological characters of pollen grains of 15 Artemisia species viz. shape of pollen, arrangement of spinules, exine sculpture, spinules base, equatorial width and polar length, were employed to construct a dendrogram following the consequential cluster analyses. In the dentrogram, four groups within the studied Artemisia species have been recognized. The pollen morphology of Artemisia could be a good taxonomic marker to cope with its taxonomic delimitations in combination with other floral and molecular attributes.